A social stigma model of child labor - López Calva, Luis Felipe (Estudios Económicos de El Colegio de México, 2002)
This paper constructs a model in which a social norm is internalized. The social disapproval of people who violate the norm -stigmatization-- is incorporated as a reduction in their utility. That reduction in utility is lower as the proportion of the population that violates the norm increases. In the model, society disapproves of people sending their children to work and parents care about that “embarrassment". An equilibrium is constructed in which the expected and realized stigma costs are the same; and the wages rates of child and adult labor are such as to equate demand and supply for each kind of labor.